Natalia Sergéyevna Goncharova (2020)
She was a main representative of the avant-garde movement of Russian painting, as well as a pioneer and founder of the so-called neo-primitivism, in which she evoked part of the traditional orthodox Christian iconography and, in turn, of Jewish and medieval themes.